Sanksi Pidana Pelatihan Kerja bagi Anak dalam Undang-Undang Sistem Peradilan Pidana Anak - Koy, Yunita Inoriti (Universitas Negeri Malang, 2021)
This study aimed to analyze the legal ratio of Article 71 paragraph (1) letter c of Law Number 11 of 2012 concerning the Criminal Justice System for Children and the concept of criminal sanctions for job training for children in the future. The type of research was normative juridical research with a statute approach and a legal concept approach. Research data were collected and analyzed descriptively. The results of the study described that the ratio legis of the inclusion of job training criminals in Article 71 paragraph (1) letter c as a form of government action in providing protection and providing interests for children who could be subject to criminal job training as sanctions for children in conflict with the law. The concept of criminal sanctions for job training for children in the future was guiding, fostering, and directing children in conflict with the law, providing job training organized by institutions formed by the government or private institutions in collaboration with the government, providing entrepreneurship training so the children could be independent and useful for society.